(untitled) (The Journal of Plant Protection Sciences, 2023)
Field experiments were conducted in two crop seasons during 2010 and 2011 with brinjal (var Muktakeshi) to evaluate the efficacy of chloro-neonicotinoid as foliar application against whitefly, Bemisia tabaci (Gennadius). Imidacloprid 17.8 SL @ 50 g a.i./ha, was found superior against whiteflies among other treatments, received low est number of whitefly population (1.55/plant) and offered maximum reduction of whiteflies (83.15%) as well as highest marketable fruit yield (146.50 q/ha). However, imidacloprid at lower doses showed nearly similar results. The other neonicotinoid, thiamethoxam also provided similar levels of protection as that of imidacloprid. The con ventional insecticide, methyl demeton (125 g a.i./ha) was less effective.